Survival Outcomes in Patients With 2018 FIGO Stage IA2–IIA2 Cervical Cancer Treated With Laparoscopic Versus Open Radical Hysterectomy: A Propensity Score-Weighting Analysis - Zhao, Wancheng; Xiao, Yunyun; Zhao, Wei; Yang, Qing; Bi, Fangfang (Frontiers in Oncology, 2021)
Objective To compare the survival and recurrence outcomes between open and laparoscopic radically hysterectomy (RH) for stage IA2-IIA2 cervical cancer based on Federation International of Gynecology and Obstetrics (FIGO) 2018. Methods Data of 1,373 early cervical cancer patients undergoing open or laparoscopic radically hysterectomy at ShengJing Hospital of China Medical University between January 1, 2013, and December 31, 2016, were retrospectively reviewed. Propensity score-based inverse probability of treatment weighting (PS-IPTW) was used to balance the covariates between the two groups. Results A total of 705 cervical cancer patients of FIGO 2009 stage IA2-IIA2 were finally enrolled in this study. After IPTW adjustment, the OS (HR = 2.095, 95% CI: 1.233-3.562, P = 0.006) and PFS (HR = 1.950, 95%CI: 1.194-3.184, P = 0.008) rates were significantly higher in the open RH (ORH) group compared with the laparoscopic RH (LRH) group. Then after re-staging according to the FIGO 2018 staging system, 561 patients still belonged to stage IA2-IIA2, 144 patients were upgraded to stage IIIC1p-IIIC2p. The ORH group had a significantly superior OS (HR = 1.977, 95%CI: 1.077-3.626, P = 0.028) and PFS (HR = 1.811, 95%CI: 1.046-3.134, P = 0.034) compared with the LRH group after PS-IPTW analysis. Furthermore, in patients with no high and intermediate risks, difference of the OS (HR = 1.386, 95%CI: 0.287-6.69, P = 0.684) and PFS (HR = 1.524, 95%CI: 0.363-6.396, P = 0.565) rates between the two groups were with no statistical meaning. Conclusions Outcomes of this retrospective cohort study were in compliance with indications for ORH recommended by the National Comprehensive Cancer Network guidelines Version 1, 2021. However, LRH showed non-inferiority for patients with no prognostic risk factors compared with ORH.